The concept of tradition in B. Pascal’s philosophy - Hudzhen, Olha (Sententiae, 2000)
The author notes that the starting point for the interpretation of Pascal’s understanding of the Christian tradition is the unity of letter and spirit, concretely embodied in the figure of Christ as the coincidence of the minimum and maximum of interpretation, of letter and spirit, of secular and sacred hermeneutics. This gives rise to a dualistic attitude to tradition: criticality and differentiated consideration with universal recognition. The author also emphasizes the importance of the concept of tradition for the formation of Pascal’s position on Descartes’ philosophy: tradition functions in Pascal’s philosophy as an explanation of the fact that there is no obvious beginning from which all philosophy can be deduced.